Band alignment and electrocatalytic activity at the p-n La0.88Sr0.12FeO3/SrTiO3(001) heterojunction - Wang, L. (2018)
Ferrite perovskites have exhibited promising p-type conductivity and oxygen evolution reaction (OER) activity. In this work, we investigate heteroepitaxial p-n junctions formed by La0.88Sr0.12FeO3 and n-SrTiO3(001). Sr substitution for La in LaFeO3 is shown to be effective for introducing p-type conductivity, lowering the optical bandgap, and enhancing electrocatalytic OER. A staggered, type-II band alignment with a large built-in potential within the LSFO forms due to the polar interface. This electronic structure facilitates charge transfer across the p-n junction and accounts for the strongly thickness-dependent extent of OER we observe.